Species diversity and biogeography of an ancient frog clade from the Guiana Shield (Anura: Microhylidae: Adelastes, Otophryne, Synapturanus) exhibiting spectacular phenotypic diversification - Fouquet, Antoine; Leblanc, Killian; Framit, Marlene; Réjaud, Alexandre; Rodrigues, Miguel Trefaut; Castroviejo-Fisher, Santiago; Peloso, Pedro Luiz Vieira; Prates, Ivan; Manzi, Sophie; Suescun, Uxue; Baroni, Sabrina; Moraes, Leandro J.C.L.; et al. (Biological Journal of the Linnean Society, 2021)
The outstanding biodiversity of the Guiana Shield has raised many questions about its origins and evolution. Frogs of the genera Adelastes, Otophryne and Synapturanus form an ancient lineage distributed mostly across this region. These genera display strikingly disparate morphologies and life-history traits. Notably, Synapturanus is conspicuously adapted to fossoriality and is the only genus within this group to have dispersed further into Amazonia. Moreover, morphological differences among Synapturanus species suggest different degrees of fossoriality that might be linked to their biogeographical history. Through integrative analysis of genetic, morphometric and acoustic data, we delimited 25 species in this clade, representing a fourfold increase. We found that the entire clade started to diversify ~55 Mya and Synapturanus ~30 Mya. Members of this genus probably dispersed three times out of the Guiana Shield both before and after the Pebas system, a wetland ecosystem occupying most of Western Amazonia during the Miocene. Using a three-dimensional osteological dataset, we characterized a high morphological disparity across the three genera. Within Synapturanus, we further characterized distinct phenotypes that emerged concomitantly with dispersals during the Miocene and possibly represent adaptations to different habitats, such as soils with different physical properties. © 2021 The Linnean Society of London, Biological Journal of the Linnean Society.
Keywords: Amazonia; Amphibia; integrative taxonomy; micro-computed tomography; mitogenomics